Observations on experimental and human paracetamol overdosage - Dixon, Michael F. (The University of Edinburgh, 1980)
This thesis records my investigations into the consequences of overdosage with the analgesic drug paracetamol. The major complication, that of hepatic necrosis, has been investigated in experimental animals using light-microscopy, electron-microscopy and histo¬ chemistry. The pathological findings in 18 fatal human cases are recorded and compared and contrasted with previous reports in the literature. A further 16 fatalities resulting from overdosage with compound preparations containing paracetamol are also reported. A variety of methods for quantifying the extent of hepatic necrosis have been evaluated, including the use of the image-analysis computer, and these methods applied to experimental and human material. In addition to morphological studies, the influence of microsomal induction on the toxic meta¬ bolism of the drug has been investigated and the effectiveness of a possible antidote, a-tocopherol, has been tested in the rat. The thesis includes chapters on the history and usage of paracetamol and on the treatment of overdosage based on reviews of the literature.